Irrigation network launch - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A new online network, aimed at exchanging experiences, innovations and research results in the field of small-scale irrigation in western and central Africa, was recently launched by Arid (Regional Irrigation and Drainage Association). The website...